The Global Consciousness Project, Identifying the Source of Psi: A Response to Nelson and Bancel - May, Edwin C; Spottiswoode, S. James P. (Journal of Scientific Exploration, 2011)
First of all we want to express our thanks to the Journal for allowing us to have the “last” word. We put last in quotes because the very good news about this exchange is that the discussion will undoubtedly continue. While it might be possible to respond point by point to Nelson and Bancel’s remarks, we prefer to focus on serious points of disagreement. We will comment upon their responses separately. Before we begin, it is important to recognize that while our interpretations differ, there are large areas of overlap in our thinking.